Communicative Failures and Their Causes as a Result of Unsuccessful Communication - Dilshatovna Shakirova, Rezeda; Renatovna Safina, Adelina; Rustyamovna Akhunzianova, Raisa (International Journal of Engineering and Technology, 2018)
The article treats the phenomenon of a communicative failure as a result of unsuccessful communication and analyses the factors leading to this occurrence. The research is based on the communicative-pragmatic method, which considers a variety of pragmatic factors affecting the realization of the communicative situation, and the descriptive method which is oriented on studying the language as a system of units and rules of their use. The illustrative basis consists of the situations expressing the meanings of epistemic possibility and epistemic necessity. The research enables us to single out six groups of reasons which can serve as factors leading to a communicative failure: disregard for the norms of social and speech etiquette, inadequate perception of the interlocutor and phenomena of the extra-linguistic reality, communicative failures as a result of the influence of the personality of the participants of communication and background information that the interlocutors possess, failure in the realization of the communicative intention of the speaker, intentional or unintentional striving for a communicative failure, inability to build a speech utterance. The indicated factors lead to the conclusion that they are often determined by the difference of an intra-cultural character, and the use of epistemic markers on the whole does not affect the success of communication.Â Â Â